Pelanggaran Prinsip Kesopanan dalam Naskah Drama Riḥlatun Ilā al-Gād Karya Taufik Al-Hakim: Analisis Pragmatik - Muhammad Izzuddin (Universitas Muhammadiyah Gorontalo, 2022)
This study describes the types of infringement of the principle of politeness in the drama script “riḥlatun ilā al-gād” by Taufik Al-Hakim. This study used three methods: the method of data collection, data analysis, and presentation of the result of the analysis. The data is collected using the listen and note method, the data analysis uses the pragmatic equivalent method, and the results of the analysis are presented informally. The results of this study found an infringement of the principle of politeness in 5 maxims: the tact maxim, generosity maxim, approbation maxim, modesty maxim, and agreement maxim, and also the infringement of the sympathy maxim was not found in this research. Some of the implicatures of infringement of the principle of politeness are implicatures for ordering, prohibiting, expelling, affirming, etc.